Intelligent Vehicular System with Speed Limit - Laxma Reddy, D; S. Arulanth, T; Nehru, K; Nagaraju, N; Ramesh Reddy, G (International Journal of Engineering and Technology, 2018)
In the scholarly world and the car business vehicular communication is one of the important point. The point of this developing interest is to build up a compelling communication network to the Intelligent Transportation System. Here in the proposed paper we exhibited remote base station model with a great put assessment. The auto movement demonstrate and lining framework with variable solicitations are used remote to get point display. The wireless networksÂ performance may beÂ compactÂ fromÂ a spreadÂ of parameters,Â equivalent toÂ radio communicationÂ vary, the quantityÂ ofÂ shoppers may varyÂ and speed of the vehicle. Some of the parameters are analyzed and displayed.Â Â Â